Fatal dual infection of avian polyomavirus and psittacine beak and feather disease virus in Chile - González-Hein,Gisela A. (Universidad Austral de Chile. Facultad de Ciencias Veterinarias, 2017)
ABSTRACT A 6 week old Plum-headed parakeet (Psittacula cyanocephala) from a private bird collection in the Metropolitan Region of Chile died after presenting depression, ataxia, tremors of the head, subcutaneous hemorrhage and delayed crop emptying. Histological examination of liver tissue revealed intranuclear viral inclusion bodies and focal necrosis. Liver tissues and blood contained both avian polyomavirus (APV) and psittacine beak and feather disease (PBFD) viral nucleic acids (DNA), indicating dual viral infection. The purpose of this report is to describe the first case of concurrent psittacine beak and feather disease virus PBFDV and APV infection in a psittacine bird in captivity in Chile. PBFDV has not been reported until now in Chile.